ChemInform Abstract: Principles of Electron Capture and Transfer Dissociation Mass Spectrometry Applied to Peptide and Protein Structure Analysis. Issue 34 (1st August 2013) - Zhurov, Konstantin O.; Fornelli, Luca; Wodrich, Matthew D.; Laskay, Uenige A.; Tsybin, Yury O.
Abstract Review: 60 refs.